ð˜šð˜±ð˜°ð˜¥ð˜°ð˜±ð˜µð˜¦ð˜³ð˜¢ ð˜§ð˜³ð˜¶ð˜¨ð˜ªð˜±ð˜¦ð˜³ð˜¥ð˜¢ (J. E. SMITH, 1797) (LEPIDOPTERA: NOCTUIDAE) CONTROL AND PRODUCTIVE PERFORMANCE OF BT MAIZE GENOTYPES - Scoton, Ana Maria Nascimento; Degrande, Paulo Eduardo; da Silva, Mariany Balbueno; Jacques, Filipe Lemos; LourenÃ§Ã£o, AndrÃ© Luis Faleiros; de Souza, Ellen Patricia (REVISTA DE AGRICULTURA, 2020)
The purpose of this work was to evaluate the yield performance of Bt maize hybrids under field conditions with damage of the Spodoptera frugiperda in a completely randomized blocks design, under a factorial scheme, with four replications. Six treatments (five Bt maize hybrids and one non-Bt hybrid) were evaluated, with and without control of the S. frugiperda. In the evaluations of number of larvae and average damage scores on maize plants there was a lower incidence and lower damage of larvae on the genotypes containing LeptraÂ® and Viptera 3Â® technologies and for the productive parameters there was no significant difference between the studied genotypes, even with and without chemical control of the pest. It was concluded that there are genotypes of corn resistant to S. frugiperda, however, there was no significant difference in the yield performance of the different hybrids when comparing the difference between lack of control and chemical control in the infestation conditions found in this study. This suggests that the levels of economic damage of S. frugiperda on corn crop are higher than the levels of infestation occurred in the study.